Microwave Assisted Exfoliation of Graphene and its Application in Enzyme Immobilization - Talat, Mahe; Awasthi, Kalpana; N. Srivastava, Onkar (Current Nanomaterials, 2016)
Background: Few layer graphene oxide was prepared by microwave irradiation which is convenient and less energy-consuming method. The enzyme immobilized graphene can be used for various applications including in the field of industrial, biomedical, waste-water treatment etc. Objective: The aim of the present study is to prepare graphene using fast and energy saving method and immobilization of Urease enzyme onto functionalized graphene sheet for various applications. Method: Few layer graphene oxides were prepared by microwave irradiation of graphite oxide. The graphene oxide was functionalized by L-cysteine and further used for the Urease enzyme immobilization. The morphology of as prepared graphene samples were investigated with the help of scanning and transmission electron microscope. Fourier-transform infrared spectroscopy was used to study the functionalities present on the graphene surface and also to confirm the attachment of urease enzyme on graphene sheet. Results: The TEM investigation revealed the transparent and smooth surface of graphene sheet. The enzyme molecules are presented nearly spherical in shapes onto the surfaces of the graphene sheet. The FTIR result confirms the presence of the amide functional groups in the enzyme immobilized functionalized graphene sample. The percentage immobilization was quite high i.e., 85% and the enzyme’s activity was also promising for the reusability. Conclusion: Microwave irradiation process results into a large volume expansion of the graphene powder. Functionalized graphene was used for the Urease enzyme immobilization. Percentage immobilization was significantly high showing 85% with enhanced stability and reusability up to ten times with significant activity.
Keywords: enzyme